Pengaruh Perlakuan Alkalinisasi Serat Alam Kayu Bangkirai (Shorea Laevifolia Endert) pada Sifat Mekanik Komposit dengan Matriks Poliester - Andromeda Dwi Laksono; Basyaruddin -; Nur Adlina (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Waste of bangkirai wood is very abundant and is not currently utilized optimally. It is known that composites using natural fibers have many advantages such as the material produced is lighter, corrosion-resistant, the availability of abundant raw materials, low production costs and natural fibers are more environmentally friendly. Natural fiber composite is a solution to the utilization of bangkirai wood waste. For optimal mechanical properties, chemical treatment of bangkirai wood fiber waste is needed. This study was conducted to determine the effect of alkalization treatment of natural fibers of bangkirai wood (Shorea Laevifolia Endert) with polyester matrix on the mechanical properties of tensile and flexural strength. The making of composites was carried out using the hand lay up method with the size of tensile test specimens that referred to ASTM D 638 and bending test specimens which referred to ASTM D 790 and from the tensile test results morphological observations were performed using Scanning Electron Microscopy (SEM).The results of this study are the optimal tensile strength values of 58.33 MPa in fiber composites with 7% alkalization treatment. As for the optimal bending strength in bending test of 65.63 MPa in fiber composites with 5% alkalization treatment. Keywords :bangkirai wood, alkalization treatment, tensile test, bending testABSTRAKJenis Kayu bangkirai terutama limbahnya sangat berlimpah dan saat ini belum dimanfaatkan secara optimal. Diketahui bahwa komposit menggunakan serat alam memiliki banyak keunggulan seperti material yang dihasilkan lebih ringan, tahan korosi, ketersediaan bahan baku yang melimpah, biaya produksi rendah serta serat alam lebih ramah lingkungan. Komposit serat alam merupakan solusi pemanfaatan limbah kayu bangkirai. Agar sifat mekaniknya optimal, perlu dilakukan perlakuan kimia pada limbah serat kayu bangkirai. Penelitian ini dilakukan untuk mengetahui pengaruh perlakuan alkalinisasi serat alam kayu bangkirai (Shorea Laevifolia Endert) dengan matriks poliester pada sifat mekanik kekuatan tarik dan kelenturan. Pembuatan komposit dilakukan menggunakan metode hand lay up dengan ukuran spesimen uji tarik yang mengacu pada ASTM D 638 dan spesimen uji bending yang mengacu pada ASTM D 790 serta dari hasil pengujian tarik dilakukan pengamatan morfologi menggunakan Scanning Electron Microscopy (SEM). Kata kunci :bangkirai wood, perlakuan alkalisasi, uji tarik, uji bending